Simil Sync/Linear Sync: Past, Present, and Future - Di Francesco, Valentina; Sileo, Angela (Journal of Audiovisual Translation, 2025)
This paper examines the emergence and evolution of simil sync in the Italian audiovisual sector, which originated in the mid-2000s as a spontaneous adaptation of voiceover techniques for non-scripted genres on thematic channels and OTT platforms. It traces changes in terminology, technical development, and recognition within the industry, also influenced by National Collective Labor Agreements (CCNLs). The study surveys Italian TV genres that shaped adaptation styles and examines the shifting role of non-automated adaptors and dubbing actors amid growing AI integration. Given the status of simil sync as a low-quality adaptation and niche modality, the concluding section explores potential future scenarios, with particular attention to the impact of AI-driven tools. Three video editing platforms – Dubverse, Vidnoz, and Wondershare Filmora 14 – were tested on a short clip containing the idiom “hit the books,” evaluated on (1) qualitative and (2) quantitative sync, (3) audio-visual/multimodal consistency, (4) translation accuracy, and (5) voice naturalness – prioritizing an accessible and audience-friendly viewing experience. Lay summary For decades, dubbing has been the predominant audiovisual translation (AVT) modality in Italy. Over time, however, alternative adaptation methods have emerged, with varying degrees of audience acceptance. This study focuses on “linear sync”, a term introduced in late 2023 to replace Sincronismo Ritmico Non Labiale (SRNL), referring to a half-synchronized adaptation process also known as “semi-sinc” (Sileo, 2018a, 2020) or “simil sync”. Officially recognized in the 2017 industry agreement, “linear sync” emerged in the early 2000s as a more efficient and cost-effective solution for adapting factual programs (Sileo, 2020). While simil sync, like standard dubbing, aims to match the duration of utterances in the target language with the original, it does not prioritize lip synchronization. This distinction has sparked debate within the AVT community: many professionals argue that it is less challenging than traditional dubbing, whereas linear sync adaptors present a different perspective on the process. Furthermore, within the Italian dubbing industry and among audiences, the AVT mode holds a complex reputation. Often regarded as a “stepchild” of standard dubbing (Barra et al., 2020), this hybrid transfer mode is sometimes criticized for its perceived simplicity and association with non-fiction content (Antoniazzi & Barra, 2020; Sileo, 2020). This paper opens with an overview of linear sync or simil sync, tracing its development from inception to its current status in Italian AVT. Building on this historical context and previous research, we conclude with insights into the future path of simil sync in terms of its potential for development and appreciation in the Italian audiovisual landscape. This study wishes to contribute to our understanding of evolving AVT practices and the factors which may shape the future of audiovisual translation in Italy.